Menghadapi Tantangan: Dampak Keluarga Broken Home pada Prestasi Akademik Anak - Dimas Julian Pratama; Muhammad Farhan Agusta; Cyndy Felisya; Sani Safitri; Syarifuddin Syarifuddin (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Broken home families can have a significant impact on children's academic achievement. This study aims to identify the impact of broken home families on children's academic achievement and develop strategies to overcome these difficulties. The results showed that children from broken home families experience difficulties in developing social skills, managing positive thoughts, and achieving optimal academic performance. The strategies developed to overcome these difficulties include building emotional support, developing social skills, managing positive thoughts, increasing learning motivation, and developing time management skills. This research has implications for the importance of providing attention and support to children from broken home families so that they can reach their full potential.